How I do it : Endoscopic Endonasal Surgery for Craniopharyngioma - Suresh Sankhla; Anshu Warade; Ghulam Muqdata Khan (Brazilian Society for Pediatric Neurosurgery, 2022)
Endonasal endoscopic surgery is currently considered as a standard method to treat a variety of suprasellar lesions including craniopharyngiomas. This infrachiasmal surgical approach provides straight trajectory and adequate exposure of the retrochiasmatic tumor and has several advantages over the conventional transcranial approaches. In this report, we describe our technique of endoscopic endonasal transtuberculum transplanum surgical approach to remove a retrochiasmatic craniopharyngioma in an 11-year old girl who presented with progressive headache, vomitings and diminution of vision since 2 weeks. Her examination revealed 6/18 vision and papilledema. Her hormonal profile was normal. MR imaging demonstrated a large solid-cystic tumor in the suprasellar region with areas of calcification within the tumor causing compression on anterior third ventricle and  obstructive hydrocephalus. She underwent insertion of VP (ventriculo-peritoneal) shunt on admission and had total tumor resection through endoscopic endonasal approach after 24 hours. Postoperatively, her headache subsided immediately and she continued to show recovery in her vision. A postoperative MR scan showed complete tumor excision.